2021
DOI: 10.1002/adfm.202110663
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Afterglow and Related Photochromism from Solution‐Grown Perovskite Crystal

Abstract: Near‐infrared (NIR) afterglow is keenly sought in emerging areas including deep‐tissue imaging and night‐vision surveillance, while only few successes in powder phosphors are achieved through solid‐state calcination. In this work, a perovskite single crystal, namely Cs2Na0.2Ag0.8InCl6:Yb3+, is grown in solution via a simple hydrothermal reaction. Through a co‐doping strategy involving both Na+ and Yb3+, dual‐band emission in the visible and NIR region is activated by self‐trapped excitons (STE) and lanthanide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 35 publications
0
47
0
2
Order By: Relevance
“…Since all the photographs were imaged under an identical illumination with a white light-emitting diode (LED), the brightness value of the crystals could be used as an accountable measure for reflectivity. To this end, the brightness (range: 0–255) of the photochromic crystal was determined using Image J and normalized ( I B ) by the following equation: 16 where I t is the integrated the area under the brightness profile at t time, and I max and I min are the corresponding areas of original and colored crystals, respectively. The detailed calculation process is shown in the ESI (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since all the photographs were imaged under an identical illumination with a white light-emitting diode (LED), the brightness value of the crystals could be used as an accountable measure for reflectivity. To this end, the brightness (range: 0–255) of the photochromic crystal was determined using Image J and normalized ( I B ) by the following equation: 16 where I t is the integrated the area under the brightness profile at t time, and I max and I min are the corresponding areas of original and colored crystals, respectively. The detailed calculation process is shown in the ESI (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Liu et al reported a perovskite single crystal which was grown in a hydrothermal reactor at 180 °C. 16 The crystal showed not only a long afterglow in the near-infrared region but also a reversible photochromism under heating. Unlike amorphous glass, such an attempt on photochromic crystals was particularly encouraging due to the integrated nature of ordered lattices, although the roles of individual dopants in varied lattice sites remained elusive.…”
Section: Introductionmentioning
confidence: 96%
“…3b), which was in agreement with previous reports. 13,14 In comparison, the afterglow of the K-doped crystal was stronger than that of the Li-doped one in the first 40 seconds (also see the photographs in Fig. 3a), but became weaker in the long run (40 to 2000 s).…”
mentioning
confidence: 89%
“…13 Through a careful manipulation of the Na + /Mn 2+ concentration, both the density and depth of afterglow traps were finely tuned, resulting in a long afterglow duration of 5400 s. Recently, Liu et al reported an afterglow crystal of chloride perovskite. 14 The emission in the near-infrared (NIR) region was activated by ytterbium ions, which enabled not only a long afterglow in the NIR band but also an associated photochromism. These advances have showcased the ability of alkali metal ions, namely Na + , to trap the tuning of afterglow.…”
mentioning
confidence: 99%
“…However, the synthesis of these inorganic materials is typically harsh and involves the use of toxic chemicals. [3,4] In contrast, organic-based LPL (OLPL) materials that possess ultralong lifetime [5][6][7] and high flexibility [8,9] at room temperature can be synthesized under environ-mentally friendly conditions. [10,11] Numerous approaches such as polymer embedding, [12,13] crystallization engineering, [14] hydrogen bonding interactions, [15] host-guest interactions, [16] and H-aggregates [17] have been developed to minimize intra-or intermolecular transport, thus achieving room-temperature LPL in pure organic materials.…”
Section: Introductionmentioning
confidence: 99%